(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
Road traffic accidents are most common cause of death in individuals less than 50 years of age. A wide pattern of injuries are seen in such accidents. Pedal cyclists are frequently involved in traffic accidents. However the incidence of fatal accidents involving pedal cyclists is extremely less. This can be attributed to the less speed of the pedal cyclists and to dedicated lanes provided. Head injuries are the most common cause of death in such accidents. However, we here present a case of accidental decapitation of a pedal cyclist on collision with a car. Evaluation of the crime scene and autopsy showed that it could have been a side on impact of the pedal cyclist by car, and the decapitation of head would have been due to the bonnet of car